Change of Subject of Formulae (Transposition of Formulae)
Topic Content:
- Change of Subject of Formulae (Transposition of Formulae)
To change or transpose a formulae means to rearrange it so that a different letter or symbol becomes the subject. This process is exactly the same as solving equations.
Remember, what is done to the LHS is done to the RHS of the formulae at all times.
e.g. I = \( \frac{PRT}{100} \)
Make P the subject of the formula
Multiply both sides by 100
⇒ \( \scriptsize 100 \: \times \: I = \frac{PRT}{100} \scriptsize \; \times \; 100 \)
⇒ 100I = PRT
Divide both sides by RT
⇒ \( \frac{100I}{RT} = \frac{PRT}{RT}\)
⇒ \( \frac{100I}{RT} = \frac{P\not{R}\not{T}}{\not{R}\not{T}}\)
P = \( \frac{100I}{RT} \)
Worked Example 8.2.1:
Make x the subject of formulae of Questions 8.2.1 a – d
a. y = x + 6
b. x2 = 10 – y
c. \( \frac{x}{5} \scriptsize = a + 2x \)
d. y = \( \scriptsize 5 \left(\sqrt{x^2 \: + \: 2}\right) \)
e. Make T the subject of the formula: P = \( \frac{nRT}{V} \)
f. Make m the subject: w = \( \sqrt {\frac{K}{m}} \)
g. T = \(\scriptsize 2 \pi \sqrt {\normalsize \frac{L}{g}}\) make g the subject
Solution
a. y = x + 6
Subtract 6 from both sides
y – 6 = x + 6 – 6
Move x (the subject) to the left-hand side
x + 6 – 6 = y – 6
x + 0 = y – 6
x = y – 6
b. x2 = 10 – y
Take the square root of both sides
⇒ \( \scriptsize \sqrt {x^2} = \sqrt{10 \: – \: y} \)
\( \scriptsize \left(\sqrt {x^2} = x\right) \)∴ x = \(\scriptsize \sqrt{10 \; – \; y} \)
c. \( \frac{x}{5} \scriptsize = a + 2x \)
Multiply both sides by 5
⇒ \(\scriptsize 5 \; \times \; \normalsize \frac{x}{5} \scriptsize = 5 \; \times \; a + 2x \)
⇒ \(\scriptsize x = 5(a + 2x) \)
⇒ \(\scriptsize x = 5a + 10x\)
Subtract 10x from both sides
⇒ \(\scriptsize x \; – \; 10x = 5a + 10x \; – \; 10x\)
⇒ \(\scriptsize -9x = 5a \)
Divide both sides by -9
⇒ \(\frac{-9x}{-9} = \frac{5a}{-9}\)
⇒ \(\frac{-\not{9}x}{-\not{9}} = \frac{5a}{-9}\)
\(\scriptsize x =\; – \; \normalsize \frac{5a}{9}\)
d. y = \( \scriptsize 5 \left(\sqrt{x^2 \: + \: 2}\right) \)
Find the square of both sides
y2 = \( \scriptsize 5^2 \left(\sqrt{x^2 \: + \: 2}\right)^2 \)
y2 = 52 (x2 + 2)
y2 = 52 x2 + 52 × 2
y2 = 52 x2 + 50
y2 = 25x2 + 50
Subtract 50 from both sides
y2 – 50 = 25x2 + 50 – 50
y2 – 50 = 25x2
Divide both sides by 25
⇒ \(\frac{y^2 \; – \; 50}{25} = \frac{25x^2}{25}\)
Move x to the left-hand side
x2 = \( \frac{y^2 \; – \; 50}{25}\)
⇒ \(\scriptsize x^2 = \normalsize \frac{y^2}{25} \; – \; \frac{50}{25}\)
i.e. \(\scriptsize x^2 = \normalsize \frac{y^2}{25} \; – \; \scriptsize 2\)
Take the square root of both sides
⇒ \(\scriptsize \sqrt{x^2} = \sqrt{\normalsize \frac{y^2}{25}} \; – \; \sqrt{\scriptsize 2}\)
\(\scriptsize x = \normalsize \frac{y}{5} \; – \; \sqrt{\scriptsize 2}\)
or
\(\scriptsize x = \normalsize \frac{y \; – \; 5\sqrt{2}}{5}\)
e. Make T the subject of the formula: P = \( \frac{nRT}{V} \)
Multiply both sides by V
⇒ \(\scriptsize P \: \times \: V = \normalsize \frac{nRT}{V} \scriptsize \; \times \; V \)
PV = nRT
Divide both sides by nR
⇒ \( \frac{PV}{nR} = \frac{nRT}{nR} \)
Move T to the left-hand side
⇒ \( \frac{nRT}{nR}= \frac{PV}{nR} \)
⇒ \( \frac{\not{n}\not{R}T}{\not{n}\not{R}}= \frac{PV}{nR} \)
T = \( \frac{PV}{nR} \)
f. Make m the subject: w = \( \sqrt {\frac{K}{m}} \)
Take the square of both sides
w2 = \( \left( \sqrt{ \frac{K}{m} }\right)^2 \)
w2 = \( \frac{K}{m}^{\frac{1}{2} \: \times \: 2} \)
w2 = \(\frac{K}{m} \)
Cross multiply
w2m = K
Divide both sides by w2
⇒ \( \frac{w^2m}{w^2} = \frac{K}{w^2} \)
⇒ \( \frac{\not{w^2}m}{\not{w^2}} = \frac{K}{w^2} \)
m = \( \frac{K}{w^2} \)
g. T = \(\scriptsize 2 \pi \sqrt {\normalsize \frac{L}{g}}:\) make g the subject
This can also be written as: T2 = \( \scriptsize2^2 \pi^2 \normalsize \frac{L}{g}^{\frac{1}{2}}\)
Take the square of both sides
⇒ T2 = \( \scriptsize2^2 \pi^2 \normalsize \frac{L}{g}^{\left(\frac{1}{2}\scriptsize \: \times \: 2\right)}\)
⇒ T2 = \( \scriptsize 4\pi^2 \normalsize \frac{L}{g}\)
Multiply both sides by g
⇒ \(\scriptsize g \: \times \: T^2 = 4 \pi^2 \normalsize \frac{L}{g}\scriptsize \; \times \; g\)
⇒ \(\scriptsize gT^2 = 4 \pi^2 L \)
Divide both sides by T2
⇒ \(\frac {g T^2}{T^2} = \frac{4 \pi^2 L}{T^2} \)
⇒ \(\frac {g\not{T^2}}{\not{T^2}} = \frac{4 \pi^2 L}{T^2} \)
g = \(\frac{4 \pi^2 L}{T^2} \)
h. f = \( \frac{1}{2 \pi LC}: \) make C the subject
Multiply both sides by 2πLC
⇒ \(\scriptsize 2 \pi LC \: \times \: f = \normalsize \frac{1}{2 \pi LC} \scriptsize \; \times \; 2 \pi LC \)
⇒ \(\scriptsize 2 \pi LCf = 1 \)
Divide by 2πLf
⇒ \( \frac{2 \pi LCf}{2 \pi L f} = \frac{1}{2 \pi Lf} \)
⇒ \( \frac{\not{2} \pi \not{L}C\not{f}}{\not{2} \pi \not{L}\not{f}} = \frac{1}{2 \pi Lf} \)
∴ \( \scriptsize C = \normalsize \frac{1}{2 \pi Lf} \)